Implementasi Bentuk-Bentuk Pendidikan dan Bimbingan Keagamaan Mental Untuk Merehabilitasi Remaja Korban Narkoba di Lapas Narkotika Kelas IIA Yogyakarta - ., Trinoto (Universitas Alma Ata, 2018)
This study examines the Implementation of Forms of Religious Guidance and Mental Development for Rehabilitation of Narcotics Victims in Narcotics Class II A Yogyakarta. The problems studied relate to rehabilitation of juvenile drug abuse at IIA Yogyakarta, forms of implementation of forms of religious guidance and mental guidance for adolescent victims of narcotics in the Class IIA Narcotics Prison Yogyakarta. This research is a qualitative research using observation method, in-depth interview, documentation and data analysis.The results of this study is the method of implementation of forms of religious guidance and mental coaching is able to prevent resdivis back in the Class IIA Narcotics Prison Yogyakarta. Coaching mental personality through Therapeutic community method and Auto suggestion able to cultivate mental and confidence in community development community, eliminating the feeling of lack of confidence and add optimistic support of community development community in living life outside social institution. Development of independence that matches the interests and talents of teenagers in the Class IIA Narcotics Center Yogyakarta is able to explore the potential talents of prisoners so that after out of prison, inmates can self-employed. Keywords: Implementation Religious form, mentoring and self-help.